The role of in‐group norms and group status in children's and adolescents' decisions to rectify resource inequalities. (12th December 2018) - McGuire, Luke; Elenbaas, Laura; Killen, Melanie; Rutland, Adam
Abstract : Children's and adolescents' resource allocation was examined in a context of inequality between schools and a peer group norm of either equality or equity. Participants ( N =  257; children, 7–11 years old and adolescents, 13–16 years old) were inducted into groups with either a lot (advantaged) or few (disadvantaged) art resources, in the context of an art competition. Participants were prescribed an equality (equal distribution) or equity (more resources for disadvantaged groups) norm, before allocating resources between groups. Adolescents, but not children, allocated significantly more resources to their disadvantaged in‐group than they did to a disadvantaged out‐group, particularly when prescribed an in‐group norm of equity. Participants who rectified the inequality referred to the unfair nature of the initial disparity. The findings revealed an important developmental shift between middle childhood and early adolescence regarding the influence of group status and norms on intergroup resource allocation in a competitive context. Statement of contribution What is already known on this subject? Children have the capacity to challenge intergroup resource allocation inequalities. Peer group norms can guide resource allocation in situations where inequality is not made salient. What does this study add? A peer group equity norm can guide adolescents to rectify an intergroup inequality. Relative peer group advantage plays an increasingly important role in adolescence. For children, maintaining equality can supersede adherence to a peer group norm.